Transitional labour market policy - CHOEURNG, Theany (KDI School, 2016)
Individual faces many problems within the labour market. School-to-work transition is an obvious social phenomenon to be witnessed that young people encounter many difficulties from education to the world of work. These difficulties are unemployment, difficulties in job searching due to the inadequate employment centers, occupational mismatch, working poor, occupational instability, and wage. Some of them are successful in getting a job while others could not get any job. The purpose of this paper is to find out key factors that contribute to successful transition from school to work in Cambodia. Based on the finding, the policy implication will be made to provide a smooth transition for the graduates or those who are leaving school. The purpose of the study will respond to two main questions: 1. What are the key determinants of successful transition from school to work? 2. What needs to be done to promote smooth transition from school to work? The data used in this study is taken from Cambodian school-to-work transition survey. 2353 of respondents who leave school are the unit of analyses. Using logistic regression analysis, we are going to see relationship between variables. The interest independent variables are using employment center, working and studying combination, gender, region, age, individual level of education, field of education, mother’s education and father’s education. The dependent variable in this study is employment status after the transition. The results are reported in odds ratio and marginal effect and discrete change of logistic regression. For the odds ratio interpretation, gender and working and studying combination have positive relationship with employment status while the rest of independent variables show no relationship. For the marginal effect for predicted probability, gender (being male), and working and studying combination have strong effects on employment status. Based on the result, at least three policy areas should be taken into consideration. Firstly, women employment program should be further focused to promote women job attainment. Secondly, a well-designed employment center should be given priority so that more employment center are build and available for job seekers to use. Last but not least, the working while studying program should be widely provided to help student get hand-on experiences.
Thesis(Master) --KDI School:Master of Public Policy,2016